VALLEJO CAMPOS, A. (2018). Adonde nos lleve el logos. Para leer la República de Platón. Madrid: Trotta. - Hoyos Sánchez, Inmaculada (Daimon Revista Internacional de Filosofia, 2020)
Reseña del libro: VALLEJO CAMPOS, A. (2018). Adonde nos lleve el logos. Para leer la República de Platón. Madrid: Trotta. 361 pp.